Gestation Length and Litter Size of New Zealand White Grade Rabbit - A. Setiaji; D. A. Lestari; S. Sutopo; Y. S. Ondho; E. Kurnianto (Jurnal Sain Peternakan Indonesia, 2021)
The purpose of this study was to examine performances and factors that influence the gestation length (GL) and litter size (LS) of New Zealand White Grade (NZW Grade) rabbits. Reproduction records of NZW Grade rabbits were taken from April 2020 to March 2021. Data analysis was carried out using the general linear model (GLM) procedure from Statistical Analysis System (SAS) University Edition V.6p.2. software. Farm showed a significant effect (P<0.001) on LS and significant season (P<0.05) on GL and LS. GL in the rainy season (31.56) was shorter than the GL in the summer (32.26), but the LS in the rainy season (7.06) was greater than the LS in the rainy season (6.37). Maintenance management should be improved to reduce the impact of the season on GL and LS NZW Grade rabbits.